Le contrôle de l’assurance au Canada - Humphrys, Richard (Assurances, 1981)
Mr. Richard Humphrys has delivered a very interesting paper on the supervision of insurance in Canada, at the last meeting of the International Association of Insurance Law in Chicago, last August. We have pleasure in presenting the French translation of this paper to our readers, with the agreement of the author. The paper is divided into five parts as follows: I - Introduction; II - The supervision and how it works; III - Legislative and constitutional aspects of the supervision; IV - The financial and technical control of operations; V - The control of assets and liabilities by the Department of Insurance. A.